Die Politische Philosophie der Staatenanerkennung - Selimi, Adis (2025)
»The Political Philosophy of State Recognition«: The recognition of states is a crucial element in many international conflicts that requires moral evaluation. This thesis offers the first systematic approach to the political philosophy of state recognition. It outlines the praxis of state recognition and highlights the increasing influence of moral considera-tions in international law. It presents and criticizes existing moral approaches to state recognition and offers a new approach based on a hybrid theory of justice and efficiency.